On the Buckling Force of Floating Ice Plates - Kerr,Arnold D (1981)
The calculation of the largest horizontal force a relatively thin floating ice plate may exert on a structure requires the knowledge of the buckling load for this floating plate. In the published literature on the stability of continuously supported beams and plates, it is usually assumed that this buckling force corresponds to the lowest bifurcation force p sub cr. However, recent studies indicate that, generally, this is not the case, and this report clarifies the situation of floating ice plates. This problem is first studied on a simple model that exhibits the buckling mechanism of a floating ice plate but is amenable to an exact nonlinear analysis. This study shows that, depending on the ratio of the rigidities of the 'liquid' and 'plate', the post-buckling branch may rise or drop away from the bifurcation point. Thus p sub cr may or may not be the actual buckling load. It is also shown that when lift-off of 'plate' from the 'liquid' takes place, the actual buckling load may drop substantially. This study is followed by analysis of a floating compressed semi-infinite plate with a straight free edge, assuming that there is no life-off. It is found that for this case there always exists a buckling load that is lower than p sub cr. According to the obtained results, the value p sub cr should be used with caution as a buckling load for floating ice plates. It is suggested that the buckling load be determined using the post-buckling equilibrium branch of the plate, taking into considertion the possibility of lift-off of the ice cover from the liquid base. (Author)